2020
DOI: 10.1177/1460408620923322
|View full text |Cite
|
Sign up to set email alerts
|

Waterproof cast liners for pediatric forearm fractures – A comparison of two products

Abstract: Introduction Waterproof lining in casting in the pediatric population is becoming more commonplace due to the improved quality of life for the child by providing patients with a higher physical functional level when compared to those with non-waterproof lining. The objective of this study is to compare patient satisfaction and outcomes of two commonly used waterproof liners. Methods A prospective, randomized-controlled trial of children with stable forearm fractures not requiring reduction was conducted. Of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…[2][3][4] These water-resistant casts allow for improvement in a patient's quality of life in terms of hygiene and activity level. [5][6][7][8] There are several synthetic water-resistant cast liners including Aquacast (Aquacast, Newwark, DE, USA), Delta Dry (BSM Medical, Charlotte, NC, USA), Wet or Dry (3M Scotchcast, St Paul, MN, USA), etc. that do not restrict exposure to water and allow for moisture to evaporate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] These water-resistant casts allow for improvement in a patient's quality of life in terms of hygiene and activity level. [5][6][7][8] There are several synthetic water-resistant cast liners including Aquacast (Aquacast, Newwark, DE, USA), Delta Dry (BSM Medical, Charlotte, NC, USA), Wet or Dry (3M Scotchcast, St Paul, MN, USA), etc. that do not restrict exposure to water and allow for moisture to evaporate.…”
mentioning
confidence: 99%
“…Multiple studies have shown water-resistant casts have similar clinical and radiographic outcomes compared with traditional cotton casts 2–4 . These water-resistant casts allow for improvement in a patient’s quality of life in terms of hygiene and activity level 5–8 . There are several synthetic water-resistant cast liners including Aquacast (Aquacast, Newwark, DE, USA), Delta Dry (BSM Medical, Charlotte, NC, USA), Wet or Dry (3M Scotchcast, St Paul, MN, USA), etc.…”
mentioning
confidence: 99%